Dietary Factors and Hidradenitis Suppurativa - Alan S. Shen; Jessica S. Johnson; Michelle Lynn Kerns (Adis, Springer Healthcare, 2023)
Abstract Hidradenitis suppurativa (HS) is a debilitating chronic inflammatory skin condition affecting hair follicles in flexural sites. Obesity is considered to be a risk factor for HS occurrence and thought to be associated with increased severity of HS symptoms. Here, we review the literature examining the impact of dietary factors on HS. Moreover, we propose potential mechanistic links between dietary factors and HS pathogenesis, incorporating evidence from both clinical and basic science studies.